2018
DOI: 10.1016/j.geoderma.2017.10.020
|View full text |Cite
|
Sign up to set email alerts
|

Characterising and linking X-ray CT derived macroporosity parameters to infiltration in soils with contrasting structures

Abstract: Soils deliver the regulating ecosystem services of water infiltration and distribution, which can be controlled by macropores. Parameterizing macropore hydraulic properties is challenging due to the lack of direct measurement methods. With tension-disc infiltrometry hydraulic properties near saturation can be measured. Differentiating between hydrologically active and non-active pores, at a given water potential, indirectly assesses macropore continuity. Water flow through macropores is controlled by macropore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(29 citation statements)
references
References 53 publications
4
20
0
Order By: Relevance
“…The variability was especially large for AF and AMW-Sub, explaining the low R 2 of the fitting with the Gardner equation. Müller et al (2018) also found lower variations in unsaturated hydraulic conductivity (between -0.7 and -0.1 m pressure head) and higher values of unsaturated hydraulic conductivities in Andosol (silt-loam) than in Gleysol (clay loam). The soils showed K s in the range of 0.37 Â 10 À5 to 1.90 Â 10 À5 m s -1 , usually associated with sandy-loam and silty-loam textures; it was higher in AM-Top and -Sub and AMW-Top and lower in AMW-Sub, AF, TF and TT (Table 3).…”
Section: Water Retention and Hydrodynamic Parametersmentioning
confidence: 72%
See 1 more Smart Citation
“…The variability was especially large for AF and AMW-Sub, explaining the low R 2 of the fitting with the Gardner equation. Müller et al (2018) also found lower variations in unsaturated hydraulic conductivity (between -0.7 and -0.1 m pressure head) and higher values of unsaturated hydraulic conductivities in Andosol (silt-loam) than in Gleysol (clay loam). The soils showed K s in the range of 0.37 Â 10 À5 to 1.90 Â 10 À5 m s -1 , usually associated with sandy-loam and silty-loam textures; it was higher in AM-Top and -Sub and AMW-Top and lower in AMW-Sub, AF, TF and TT (Table 3).…”
Section: Water Retention and Hydrodynamic Parametersmentioning
confidence: 72%
“…Duwig et al (2008) coupled dye infiltration with image analysis to illustrate finger-type flows in the same Mexican allophanic Andosols. More recently, X-ray tomography was used to quantify pore morphological parameters of Andosols and was coupled with hydrological analyses (Vingiani et al 2015;Müller et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…CT may also be used for imaging the whole soil core samples where a voxel size between 20 µm and 50 µm is achieved (Jarvis et al, 2017;Rab et al, 2014;Vaz et al, 2011). A resolution of this order allows for macropore observation (Jarvis, 2007;Katuwal et al, 2018;Müller et al, 2018) and root visualization (Daly et al, 2018;Sander et al, 2008). However, it can also be used for imaging soil aggregates with a voxel size of 1 µm or smaller (Józefaciuk et al, 2015;Voltolini et al, 2017b).…”
Section: Introductionmentioning
confidence: 99%
“…A 3D image obtained with this technique, following its processing, allows researchers to examine the inner structure of soil, and to collect information about pore distribution (Hu et al, 2015) and pore properties, such as shape factors (Elliot et al, 2010), connectivity (Sleutel et al, 2008) or pore circularity (Yang et al, 2018). The link between soil cores macroporosity and saturated water conductivity has been of special interest (Gerke, 2012;Larsbo et al, 2016;Müller et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The estimation of dag and the change of wf over depth is not solved yet and, considering the outcomes of this study, should be topics of future research. Some methods have been proposed in the literature for dag (Kroes et al, 2017;van Schaik et al, 2010), and the variation in field conditions of wf over depth may be measured by X-ray computer tomography (Müller et al, 2018).…”
Section: Simulations Resultsmentioning
confidence: 99%